International regulation for the use of Nuclear Power Sources in outer space: status quo, shortcomings and possible ways out - Yang, Kuan; Hassan, Manzoor (Acta astronautica, 2025)
As humans are set to explore the solar system and beyond, nuclear energy emerges as a critical enabler for long-term missions, offering enhanced efficiency, speed, and sustainability. However, potential challenges arise with human exploration of the Moon, Mars, outer reaches of the solar system, and deep space, including significant technological, sustainability, and regulatory challenges. Utilization of Nuclear Power Sources (NPS) in space is subject to national and international regulations that aim to ensure the safety, security, and sustainability of outer space, earth, and other celestial bodies. However, these regulations face challenges due to rapid technological development and difficulties in oversight and enforcement. This paper synthesizes human activities in space on celestial bodies powered by NPS. It analyzes the short-term and long-standing effects of NPS utilization and the current international regulations of NPS use. It then highlights the need for more effective regulation of NPS use by fostering cooperation and addressing the gaps in existing international regulation. Finally, the paper proposes suggestions to fill the gaps in existing international regulation and presents possible ways forward. •International regulations for the use of nuclear power sources in outer space.•Loopholes in framework for nuclear power sources in space are evident.•Domestic laws and practices of major space-faring nations are crucial.•Latest NPS regulation developments sunder UNCOPUOS framework are relevant.•Space NPS regulation needs Comprehensive and Legally Binding Framework.